PRODUKSI ALFA-AMILASE OLEH ASPERGILLUS ORYZAE DALAM MEDIA PATI SAGU (Metroxylon sp.) - S. Pudjiraharti; L. Z. Udin; A. T. Karossi (Research Center for Chemistry - LIPI, 1997)
The production 0f alpha-amylase in sago starch media by A. oryzae have-been performed in Biostat-B stirred tank fermentor with working volume of 2 L. The condition was adapted from the fermentation using Biotech fermentor: working volume 4 Liters, temperature 27°e, aeration 0,75 wm and agitation of 300 rpm. The concentrations of inoculum added into the medium were 2,5 - 3% v|v. The maximum enzyme speslfic activites around 300-460 U|g protein was obtained at fermentation using inoculum concentration of 2,5%, while the maximum enzyme specific activity of 850 U|g protein was also obtained at fermentation using inoculum concentration of 3%. The maximum enzyme specific activity was achieved at day 5 or 6 of fermentation.Fermentation using various concentrations of inoculum in erlenmeyer flask scale was carried out to investigate the inoculum concentration which resulting maximal enzyme activity. The concentrations used were 5.0%; 7.5%; 10%; and 12.5% v|v. Fermentation was done at 30°C and agitation of 120 rpm. The highest enzyme activity of 12,640 Vlg protein was resulted at fermentation with inoculum concentration of 12.5% v|v at day-5. Application into fermentator two liters at temperature 30°C, aeration 1.5 vvm and agitation of 500 rpm showed enzyme production in earlier time (one day fermentation) to achievedenzyme activity of around 1000-1300 U|g protein.